2020
DOI: 10.1002/cpdd.784
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Simulation of the Pharmacokinetics and Target Engagement of an Antagonist Monoclonal Antibody to Interferon‐γ–Induced Protein 10, BMS‐986184, in Healthy Participants to Guide Therapeutic Dosing

Abstract: BMS-986184 is a human, second-generation, anti-interferon-γ-induced protein 10 (IP-10) monoclonal antibody. In this study the pharmacokinetics and target engagement (TE) of BMS-986184 in healthy participants were characterized using population-based target-mediated drug disposition (TMDD) modeling and data from a first-in-human study (NCT02864264). The results of the first-in-human study and the model generated were used to conduct stochastic simulations of a virtual population of healthy participants to predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…The primary and secondary endpoints were not met, but higher doses were associated with increased clinical response and histological improvements, and treatment was determined to be safe. A promising second-generation human IP-10 monoclonal antibody (BMS-986184) has also been developed [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The primary and secondary endpoints were not met, but higher doses were associated with increased clinical response and histological improvements, and treatment was determined to be safe. A promising second-generation human IP-10 monoclonal antibody (BMS-986184) has also been developed [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Clinically tested effects of galcanezumab dose (120 mg and 240 mg), validated through PK modeling, indicated a steady decrease in the concentration of free ligands resulting in the development of efficacious dose regimens [163]. A PK and target engagement (molecular interaction) study of anti-interferon-γ-induced protein 10 (IP-10) mAb was characterized, which concluded optimal dose strategy and scheduling of drug administration, i.e., approximately eight subcutaneously delivered dose intervals were required weekly in this case to reach steady state [164].…”
Section: Pharmacokinetics-pharmacodynamicsmentioning
confidence: 99%
“…160 A PK and target engagement (molecular interaction) study of anti-interferon-γ-induced protein 10 (IP-10) mAb was characterized, which concluded optimal dose strategy and scheduling of drug administration, i.e., approximately eight subcutaneously delivered dose intervals were required weekly in this case to reach steady state. 161 Specialized cell-based bioassays or potency assays, including ELISA, binding assays, competitive assays, cell signaling, ligand binding, proliferation, and proliferation suppression, are essential in ascertaining the mechanism of action and similarity with the parent molecule. On the other hand, functional tests related to the possible MOA, such as apoptosis, complement-dependent cytotoxicity, antibody-dependent cellular phagocytosis, and antibody-dependent cellular cytotoxicity, among others, are necessary but not essential and also when it is not relevant.…”
Section: Pharmacokinetics-pharmacodynamicsmentioning
confidence: 99%